a right-angled triangle has base 2x + 1, height h and hypotenuse 3x. show that h^2 = 5x^2 - 4x - 1

initially, explain Pythagorean's Theory --> a^2 + b^2 = c^2.explain c is the hypotenuse, a and b can be either base or height.using a as base and b as height, a = 2x+1. b = h. c = 3xsubstitute into formula:(2x+1)^2 + h^2 = 9x^2expanding brackets (using FOIL):4x^2 + 4x + 1 + h^2 = 9x^2rearranging so h^2 is the subject:h^2 = 5x^2 - 4x - 1

MA
Answered by Mohammad A. Maths tutor

2834 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

13/2 - 5/3 = ?


Where and why do we plot points on cumulative frequency graphs?


Express 280 as a product of its prime factors.


Write 36 as a product of its prime factors giving the answer in index form.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences